Referral practices of medical practitioners in central South Africa to physiotherapy services for patients living with musculoskeletal conditions - Roline Y. Barnes; Alida Janse van Rensburg; Jacques E. Raubenheimer (AOSIS, 2021)
Background: Musculoskeletal diseases (MSDs) are a major cause of disability worldwide. It is essential to address effective MSD management, including appropriate referrals to physiotherapists and other healthcare professionals. Limited information is available regarding the referral practices of medical practitioners for patients with MSD. The doctors' referral practices to physiotherapists can impact the patient population and the South African health system. Objectives: To investigate or understand the referral practices of medical practitioners in Bloemfontein, South Africa, to physiotherapy services, for individuals living with MSD. Method: A quantitative study approach, implementing a semi-structured questionnaire, was used. Forty-nine participants completed the questionnaire. Results: The referral of patients with MSDs by medical practitioners to physiotherapy services varied and multidimensional factors influenced their referral practices. Medical practitioners were unsure of the specific role played by physiotherapists in the management of individuals living with MSD. A need for improved relationships and communication between medical practitioners and physiotherapists was identified. Conclusions: Medical practitioners regularly referred individuals living with MSD to physiotherapists, but referral practices should be optimised in terms of evidence-based practice and the use of specialised physiotherapy services. In an attempt to decrease the burden of MSD, adequate awareness should be created for improved referral practices between medical practitioners and physiotherapists. Clinical implications: Collaborative development of detailed guidelines for apt, evidence-based referrals should be developed, to ensure early detection and management of individuals living with MSD. Health care professionals should be educated and encouraged to refer individuals living with MSD to physiotherapists for appropriate management with clinical benefits including improvement of HRQOL and cost effectiveness of this management not only to the individual but also to the health system in South Africa. Physiotherapists should try to communicate their role in the treatment of individuals living with MSD to medical practitioners for the benefit of the patient.